59.2k views
0 votes
Please show all of the steps to solve the Algebra math problems below.Evaluate the following.|10| = |-4| =Subtract. Write your answer as a fraction in simplest form.5/8 � 3/8 =Subtract.7/8 � 5/6Write your answer as a fraction in simplest form.Multiply.6*(-7/2) =Write your answer in simplest form.Divide. Write your answer as a fraction or mixed number in simplest form.6/5 / (- 12/25) =Evaluate.3 + 4^2 * 2 =Evaluate.2/3 + 5/6 * � =Write your answer in simplest form.Evaluate-16 - 12 / (-4) =Use the distributive property to remove the parentheses.-9(3w � x � 2) =Simplify.-2(w + 2) + 5w =Simplify the following expression.16x^2 + 8 � 10x � 2x^2 � 14x =Evaluate the expression when b = -5 and y = 6b � 9y =Evaluate the expression when y = -3Y^2 + 5y � 4 =Evaluate.(-4)^3 =(-7)^2 =Evaluate. Write your answers as fractions.3/5^3 =(-1/3)^2 =Evaluate the expressions.(-7)^0 =2(1/3)^0 = Multiply.3v^2(-5v^4) =Simplify your answer as much as possible.Multiply.2y^2w^4*6y*2w^8 =Simplify your answer as much as possible.Simplify.(4p^3/3p^7)^-2 =Write your answer using only positive exponents.Simplify.X^-2/x^-3 =Write your answer with a positive exponent only.

User Rdubya
by
4.8k points

2 Answers

3 votes

Answer: So 5 + x = 8 beacase x is 3

Explanation:

User Nicola Uetz
by
5.2k points
5 votes

Answer:

See Explanation

Explanation:

Please note that I'll replace all � with +

1. |10|

This implies the absolute value of 10 and it always returns the positive value;

Hence;


|10| = 10

2. |-4|

Using the same law applied in (1)


|-4| = 4

3. 5/8 - 3/8 = ?

Take LCM


= (5 - 3)/(8)

Subtract the numerator


= (2)/(8)

Divide the numerator and denominator by 2


= (1)/(4)

Hence:


(5)/(8) - (3)/(8) = (1)/(4)

4. 7/8 - 5/6

Take LCM


= (21 - 20)/(24)


= (1)/(24)

Hence;


(7)/(8) - (5)/(6) = (1)/(24)

5. 6 * (-7/2)


= 6 * (-7)/(2)

Multiply the numerator


= (-42)/(2)


= -21

Hence:


6 * (-7)/(2) = -21

5. 6/5 /(-12/25)


= (6)/(5) / (-12)/(25)

Change the divide to multiplication


= (6)/(5) * (-25)/(12)

Divide 6 and 12 by 6


= (1)/(5) * (-25)/(2)

Divide 5 and 25 by 5


= (1)/(1) * (-5)/(2)


= (-5)/(2)

Hence;


(6)/(5) / (-12)/(25) = (-5)/(2)

6. 3 + 4^2 * 2


= 3 + 4^2 * 2

Solve the exponent


= 3 + 16 * 2

Apply B.O.D.M.A.S


= 3 + 32


= 35


3 + 4^2 * 2 = 35

7. 2/3 + 5/6


= (2)/(3) + (5)/(6)

Apply LCM


= (4 + 5)/(6)


= (9)/(6)

Divide the numerator and denominator by 3


= (3)/(2)

Convert to mixed fraction


= 1(1)/(2)

Hence;


(2)/(3) + (5)/(6) = 1(1)/(2)

8. 16 - 12/(-4)


= 16 - (12)/(-4)

Solve the fraction


= 16 - (-3)

Open the bracket


= 16 + 3


= 19

Hence;


16 - (12)/(-4) = 19

9. -9(3w + x + 2)


= -9(3w + x + 2)

Open brackets: Distributive property


= -9*3w -9* x -9 * 2


= -27w -9 x -18

Hence;


-9(3w + x + 2) = -27w -9 x -18

10. -2(w + 2) + 5w


= -2(w + 2) + 5w

Open bracket: using distributive property


= -2*w -2 * 2 + 5w


= -2w -4 + 5w

Collect Like Terms


= 5w-2w -4


= 3w -4

Hence;


-2(w + 2) + 5w = 3w- 4

11. 16x^2 + 8 + 10x + 2x^2 + 14x


= 16x^2 + 8 + 10x + 2x^2 + 14x

Collect Like Terms


= 16x^2 + 2x^2 + 10x + 14x+ 8


= 18x^2 + 24x + 8

Expand the expression


= 18x^2 + 12x + 12x + 8

Factorize:


= 6x(3x + 2) + 4(3x +2)


= (6x + 4)(3x +2)

Hence;


16x^2 + 8 + 10x + 2x^2 + 14x = (6x + 4)(3x +2)

12. b = -5 and y = 6


b + 9y =?

Substitute -5 for b and 6 for y


= -5 + 9 * 6


= -5 + 54


= 49

Hence;


b + 9y = 49

13. y = -3


y^2 + 5y + 4 =?

Substitute -3 for y


= (-3)^2 + 5(-3) + 4

Open all brackets


= 9 -15 + 4


= -2

Hence;


y^2 + 5y + 4 = -2

14.


(-4)^3

Open bracket:


= -4 * -4 * -4


= -64

Hence;


(-4)^3 = -64


(-7)^2

Open bracket:


= -7 * -7


= 49

Hence;


(-7)^2 = 49

15. Express as fractions:


(3)/(5^3)

Evaluate the denominator


= (3)/(125)

Hence:


(3)/(5^3) = (3)/(125)


((-1)/(3))^2

Evaluate the exponent


= ((-1)/(3))*((-1)/(3))


=(1)/(9)

Hence:


((-1)/(3))^2=(1)/(9)

16. Evaluate


(-7)^0 =

Evaluate the exponent


(-7)^0 = 1


2 * (1/3)^0

Evaluate the exponent


= 2 * 1


= 2

Hence;


2 * (1/3)^0 = 2

17. Evaluate


3v^2(-5v^4)

Open bracket


= 3 * v^2*-5* v^4

Reorder


= 3 *-5* v^4 * v^2


= -15* v^4 * v^2

Apply law of indices


= -15* v^(4 +2)


= -15* v^6


= -15v^6

Hence:


3v^2(-5v^4) = -15v^6

18.


2y^2w^4*6y*2w^8

Rewrite as


2 *y^2 * w^4*6 * y*2 * w^8

Reorder the terms


=2*6 * w^4 * w^8*y^2 * y*2


=12 * w^4 * w^8*y^2 * y*2

Apply law of indices


=12 * w^(4+8) *y^(2+2)


=12 * w^(12) *y^4


=12 w^(12) y^4

Hence:


2y^2w^4*6y*2w^8 =12 w^(12) y^4

19.


((4p^3)/(3p^7))^(-2)

Apply law of indices


= ((4p^(3-7))/(3))^(-2)


= ((4p^(-4))/(3))^(-2)

Apply law of indices


= ((4)/(3p^4))^(-2)

Apply law of indices


= ((3p^4)/(4))^(2)


= ((3p^4)/(4)) * ((3p^4)/(4))

Evaluate


= (9p^8)/(16)

Hence;


((4p^3)/(3p^7))^(-2) = (9p^8)/(16)

20.


(x^(-2))/(x^(-3))

Apply law of indices


= x^(-2 - (-3))


= x^(-2 +3)


= x^1


= x

Hence:


(x^(-2))/(x^(-3)) =x

User DChaplin
by
4.7k points